On Delayed Choice and Contingent Absorber Experiments. (30th November 2011) - Kastner, R. E.
Abstract : It is pointed out that a slight variation on the Wheeler Delayed Choice Experiment presents the same challenge to orthodox quantum mechanics as Maudlin-type contingent absorber experiments present to the Transactional Interpretation (TI). Therefore, the latter cannot be used as a basis for refutation of TI.